TMOD-36. PRECISE INVESTIGATION OF CANCER STEM CELLS IN A MOUSE GLIOBLASTOMA MODEL. (5th November 2018) - Xie, Xuanhua; Laks, Dan; Sun, Daochun; Poran, Asaf; Laughney, Ashley; Belenguer, German; Massague, Joan; Zhou, Xiuping; Farinas, Isabel; Elemento, Olivier; Parada, Luis
Abstract: Cancer stem cells (CSCs) have been shown to play a critical role in glioblastoma (GBM) pathogenesis. However, a precise and thorough understanding of these cells is still lacking. Here we design a novel mouse model to label, purify, and study cancer stem cells in vivo . Firstly we generate and characterize a new transgene to label neural stem/progenitor cells in the subventricular zone (SVZ) with GFP, and drive expression of CreERT2 and human diphtheria toxin receptor in the same cells ( CGD: nestin-CreERT2-H2BeGFP-hDTR ). Following analysis with both bulk and single cell RNA sequencing of the SVZ tissue demonstrate its faithful expression in the stem/progenitor cell compartment. We then crossed the transgene with floxed alleles of the top three mutated tumor suppressor genes in GBM patients. This genetic configuration (CGD-M4: CGD; Nf1 fl/+ ;p53 fl/+ ; Pten fl/+ ) efficiently promotes brain tumors initiated from wild-type neural stem/progenitor cells. Investigation of the tumors showed the CGD-GFP+ cells are quiescent in vivo, yet form more spheres in vitro than the GFP- cells. Further analysis with serial transplantation assays demonstrated the GFP+ cells are more competent to develop tumors and continuously maintain a quiescent population in the transplanted tumors. Diphtheria toxin treatment eliminates the CGD-GFP+ cells through the hDTR receptor in the transgene and greatly reduces the tumor bulk. The conventional chemotherapeutic drug, temozolomide, benefits only GFP- cell transplanted mice but not GFP+ cells. These cells are collected for RNA sequencing to identify genes associated with the CGD-GFP+ cells. Following CRISPR candidate screen reveals genes essential for the CGD-GFP+ cells. This study provides an unprecedented mouse model to study CSCs, which demonstrates their essential role in GBM initiation, recurrence, and drug resistance.